Parental health in the context of public family care proceedings: A scoping review of evidence and interventions. (June 2023) - Grant, Claire; Radley, Jessica; Philip, Georgia; Lacey, Rebecca; Blackburn, Ruth; Powell, Claire; Woodman, Jenny
Abstract: Background: Child protective services (CPS), or their equivalent, have statutory power to remove children from birth parents in instances of child abuse, neglect, or concerns around parenting capacity via public family care proceedings. Parents who have children subject to proceedings, 'birth parents', often have complex health and social care needs. Objective: We aimed to review what is known about the health needs of birth parents and the interventions implemented to support these health needs. Methods: We searched PubMed, Scopus, and grey literature using a systematic strategy of key concepts "health", "care proceedings", and "parents". We included all publications in English that reported parental health in the context of care proceedings from the 1st of January 2000 to the 1st of March 2021. Results: Included studies ( n = 61) reported on maternal health (57 %) or the health of both parents (40 %), with only one study reporting on fathers alone. We conceptually categorised parental health need ( n = 41) into i) mental health, ii) physical health, iii) substance misuse, iv) developmental disorders, and v) reproductive health. Health inequities and poor access to services were described across all categories, with longstanding issues often pre-dating proceedings or the child's birth. All interventions supporting parental health ( n = 20) were targeted at mothers, with some supporting fathers ( n = 8), formally or informally. We grouped similar interventions into three types: alternative family courts, wrap-around services, and specialist advocacy/peer support. Conclusions: Parents who have children subject to care proceedings have complex health needs that pre-date CPS concerns. The studies included in our review strongly suggest that health issues are exacerbated by child removal, triggering deteriorations in mental health, poor antenatal health for subsequent pregnancies, and avoidable mortality. Findings highlight the need for targeted and timely intervention for parents to improve whole-family outcomes. There are models that have been designed, implemented, and tested using relationship-based, trauma-informed, multidisciplinary, family-focused, and long-term approaches.